2019
DOI: 10.31459/turkjkin.530881
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological profile of knee injury pattern among different divisional football players

Abstract: Complete scenario of number and factors of knee injuries among the male footballers is intangible; therefore, it would seem essential to compute the injuries in relation to field condition and to show the nature and type of injuries including the possible risk factors. In a total of 200 of 215 soccer athletes playing at least one year professionally were randomized with the age range 14-40 years recruited from different divisional clubs. All information collected through questionnaires from five football clubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…July month found the pick (69.0%) level of injury among the twelve months season. Most of the researchers observed that a lower number of athletes consulted by the physiotherapists than physicians where physician managed 47.4% and athletes treated by physiotherapist 39.6% [18] In this study also found the least number visited to physiotherapy and highest numbers to others profession (Table - Sport injury rate increases with the level of play (grade in school) like; player age, and experience [19]. The lower extremity (knee and ankle joints) is most frequently injured body part among the footballer and most injuries severity are mild, including contusion, strain and sprain [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…July month found the pick (69.0%) level of injury among the twelve months season. Most of the researchers observed that a lower number of athletes consulted by the physiotherapists than physicians where physician managed 47.4% and athletes treated by physiotherapist 39.6% [18] In this study also found the least number visited to physiotherapy and highest numbers to others profession (Table - Sport injury rate increases with the level of play (grade in school) like; player age, and experience [19]. The lower extremity (knee and ankle joints) is most frequently injured body part among the footballer and most injuries severity are mild, including contusion, strain and sprain [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Sports injuries are common, yet an unwanted aspect of participation in sports (Lower, 1996;Khan et al, 2019). The characteristics of soccer along with the functional activities, which include acceleration, deceleration, jumping, cutting, pivoting, turning, lateral and backward displacement, heading and kicking of the ball, and contact with other players, obviously places great demands on the technical and physical skills of individual players.…”
Section: Introductionmentioning
confidence: 99%